Designing and developing museum visits and art education workshops with cyanotype for people with Alzheimer's. (1st December 2017) - Carmen Moreno-Sáez, María del; Ávila-Valdés, Noemí; Belver, Manuel H.; Gutiérrez-Párraga, María Teresa; Hernández, Clara; Torres-Vega, Sara
This article describes the programme Tenemos cita con el arte, involving two visits to the Prado Museum and four visual arts creativity workshops using the cyanotype photographic printing technique, designed for people affected by Alzheimer's and their caregivers. The programme is part of a larger nationwide research project that aims to make art and art education more accessible to people affected by Alzheimer's and other dementias and their caregivers, giving them an opportunity for taking part in an arts-focused programme that alternates museum visits and visual arts creativity workshops.